Schwann cell-axon metabolic interactions of the mouse sciatic nerve - Rich, Laura (2017)
In the Peripheral nervous system (PNS), akin to the central, glial cells, Schwann cells and astrocytes, respectively, contain glycogen, which is glycolytically metabolised to lactate and transported to axons for oxidative metabolism. In the PNS, however, only the myelinated A fibres, not the unmyelinated C fibres, benefit. Using in vitro electrophysiology to simultaneously record A and C fibre conduction of the mouse sciatic nerve, I investigated the metabolic interactions between Schwann cells and axons, particularly during fructose metabolism. Increased maintenance of A fibre conduction compared to C fibres in the absence of energy substrate confirmed that A fibres benefit from glycogen-derived lactate. Metabolic inhibitors, iodoacetate and cyanide, implied a preference for both glycolytic and oxidative metabolism by the A fibres, whereas C fibres survive solely on oxidative metabolism, and Schwann cells on glycolysis. C fibres required lower fructose concentrations (10mM) than the A fibres, but even in the presence of higher concentrations (20mM) recovery of A fibre conduction as a result of an absence of energy substrate was slow. This implied C fibres would express fructokinase (low Km) not the A fibres, but instead would metabolise fructose via hexokinase (high Km). However, immunohistochemistry revealed fructokinase expression by all axons and not Schwann cells. Inhibition of lactate transport with fructose as the sole energy substrate reduced the maintenance and recovery of A, but not C, fibre conduction, suggesting a need for fructose-derived lactate from the Schwann cells by A fibres. Despite this, lactate biosensors recorded lactate released from the nerve into the surrounding bath prior to recovery of A fibre conduction with 20mM fructose. A possible explanation for the slow recovery and presence of extracellular lactate is the apparent glycolytic requirement of the A fibres, which is delayed due to the Schwann cells requirement for high concentrations limiting the access to fructose. The results are consistent with a model in which A fibres metabolise fructose directly, as do C fibres, but also metabolise Schwann cell fructose-derived lactate.